Characterisation of tack for automated tape laying - Crossley, Richard James (2011)
Automated Tape Laying (ATL) trials using low cost wind energy suitable material and mould tools have been conducted. New materials proved problematic during ATL lay-up and observations of the ATL process show that the prepreg tack and stiffness properties significantly affect lay-up performance. Prepreg tack has not been widely researched within the composites industry due to the absence of a standardised method for characterisation. A new tack and stiffness test has therefore been developed which is representative of the ATL process. The new test was used to investigate the response to process and material variables. Two failure modes were observed and compared to those found in Pressure Sensitive Adhesives (PSA). Failure modes are associated with the viscoelastic stiffness of the resin. High stiffness appears to result in interfacial failure turning to cohesive failure when stiffness is reduced. A peak in tack is observed to correspond with the transition in failure mode leading to the conclusion that prepreg tack is the result of a chain system rather than a single property. The chain system consists of an interface and bulk components each having individual time and physical variable dependant properties.